Mortgage loan/financing: a comparison between conventional and islamic products and features of Malayan Banking Berhad (MBB) / Wan Ahmad Zakirin Wan Mus - Wan Mus, Wan Ahmad Zakirin (2010)
Malaysia is one of the world financial centres for Islamic finance outside the Middle East. The purpose of the study was to find out the choice criteria for home financing among Malayan Banking Berhad customers which is the biggest bank in Malaysia. There are a few sample of Malayan Banking Berhad home financing products customer among public servants, private sector workers, and self- employment were chosen as respondent. This study is to define the products and features of Conventional Mortgage Loan and Islamic Mortgage Financing of Malayan Banking Berhad and to identified which the features and characteristics which one is the most chosen one by the consumer. Nowadays, banking plays a great role in home financing. In 1830, Malaysia has started a conventional banking and since from that home financing at Malaysia had been monopolized by conventional bank. Despite the establishment of Tabung Haji in the early history of Islamic Banking in Malaysia started in 1963, the main function only focused on money saving for Hajj. In 1983, the establishment of Bank Islam Malaysia Berhad (BIMB) brought up Islamic banking as an alternative for conventional banking. Parallel with BIMB establishment, Malaysia was the pioneer of dual banking concept which means the product of Islamic and conventional banking offered by a single institution. The Malayan Banking Berhad (Maybank) started their operation in 1960 by Khoo Teck Puat and which is the biggest banking institution in Malaysia nowadays. Currently, Maybank has 450 branches around the world and 361 of them in Malaysia. The Headquarter of Maybank located at Kuala Lumpur and has over 2000 automatic transaction machine (ATM) around Malaysia. Maybank Financial Group, owned asset amounting USD 64 billion which makes this group short listed as a second place on Bursa Malaysia. The image and reputation of Maybank as the biggest bank in Malaysia trigger the possibilities of holder to make transaction. If explored choice criteria from Islamic Financing, indeed, the choice criteria proposed by these studies largely are for a conventional mortgage provider rather than an Islamic mortgage provider. Generally, this study tends to provide an insight that is useful to better reflect the choice criteria for Islamic home financing in Malaysian Islamic banking. Investigating Islamic home financing enables practitioner and academics to gain a deeper insight into the various choice criteria that accurately reflects an Islamic point of view. Thus, this research comprises two objectives; to investigate choice criteria for Islamic and conventional home financing offered by Malayan Banking Berhad.